Is community radio an effective tool for health education? Perceptions of stakeholders of a community radio project in north coastal Andhra Pradesh - Rajana, Vijay; Prasad, K. K. L.; Madhavi, B. Devi (International Journal Of Community Medicine And Public Health, 2020)
Background: Unlike commercial radio, community radio works with local communities and helps in catering their specific needs and necessities and works as an innovative tool in bringing social change by using the participation of common man from the community in the program. Community radio stations are operated, owned, and influenced by the communities they serve. The objectives of the study were to describe the background information of the community radio services and to assess the perceptions of the rural community about the effectiveness of community radio and challenges in delivering its services. Methods: This study was designed on mixed method approach. Knowledge about health was assessed through a cross-sectional study. Perceptions about the effectiveness of community radio were gathered through focus group discussions. In-depth interviews with service providers obtained limitations and constraints that hinder the effectiveness. Villages surrounding an engineering college in Srikakulam district of north coastal Andhra Pradesh which is being provided community radio services by the institute. People in the selected villages who were provided community radio services and the staff of the engineering college involved in the program. Results: Preliminary results indicate that the beneficiaries found that programmes on care during pregnancy and delivery related issues were most beneficial. Drop out of trained community personnel to provide the health education was a major drawback as per the service providers. Conclusions: This beneficial approach to community needs support from the Government to implement it in every remote corner of our country.